Monitoring the physical demands of training in Rugby League: the practices and perceptions of practitioners - Hudson, S.; Fish, M.; Haines, M.; Harper, L. (Science and Medicine in Football, 2024)
The physical demands of elite sport are often monitored with the aim of making evidence-based decisions to enhance performance and reduce injury risk. However, there is limited evidence in rugby league of the monitoring practices and perspectives of practitioners. This study provides a cross-sectional view of practices and perspectives of rugby league practitioners engaged in monitoring the physical demands of training. Practitioners from the Super League, Championship and National Rugby League competitions completed an online survey. Questions related to the tools and measures used to monitor training, along with perceptions of monitoring effectiveness. `Enhancing performance` was considered the most important factor for monitoring training demands with most practitioners using some form of time motion analysis (e.g., GPS) or accelerometers. Nearly all practitioners combined objective external measures of exercise intensity with subjective measures, of which RPE was most common. The monitoring parameters considered most useful were running metrics (high-speed running, total distance covered, and the number of accelerations). Findings suggest that current practices are mostly supported by evidence from research. There was a preference for internal load monitoring tools that are quick and simple, such as RPE. The extent to which training load was monitored was lesser in some Championship teams compared to those in the other competitions, which might be explained by discrepancies in funding and access to players.